VISUALISASI PENGAJARAN, PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT YAYASAN PENDIDIKAN DAN KEBUDAYAAN DHARMA WACANA - Kesumaningrum, Chrisensia Puspa; Muharni, Sita (LPPM Institut Teknologi Bisnis Dan Bahasa Dian Cipta Cendikia, 2023)
At the Dharma Wacana Metro Education and Cultural Foundation, the delivery of information about the implementation of the Tri Dharma is considered not to be able to run well, this is because there is no special supervision carried out to evaluate whether the Tri Dharma of Higher Education has gone well. Making Data Visualization of Tri Dharma Lecturers at the Dharma Wacana Education and Culture Foundation can make it easier to supervise the running of Tri Dharma and also make data presented in an easy-to-understand display and the data display will be more attractive. Making Data Visualization using Cloud Application Data Studio, the method used for Data Visualization of Tri Dharma Lecturers at the Dharma Wacana Education and Culture Foundation is CRISP-DM (Cross Industry Standard Process for Data Mining). The results obtained from the Visualization of Lecturer Data at the Dharma Wacana Education and Culture Foundation are considered to have not carried out the Tri Dharma optimally. From the percentage of each university, lecturers who carry out the Tri Dharma of Higher Education are: STISIPOL 52.9%, STMIK 75.8%, STIPER 63.3% and AKPER 74.4%.